Potential anti-obesity/inflammatory flavonoid-derived biomolecules against Obesity to prevent WAT differentiation by targeting a DNA-binding protein inhibitor, ID-1: Flavonoid-derived biomolecules targeting a DNA-binding protein inhibitor, ID-1 - Alanazi, Jowaher S.; Unnisa, Aziz; Alanazi, Muteb S.; Alharby, Tareq N.; patel, Rama Devi; Itumalla, Ramaiah; Younes, Kareem M.; Abouzied, Amr S.; Lakshmi K, N V C (Cellular and Molecular Biology, 2023)
A concoction of unhealthy eating, inactivity, and the adverse effects of specific drugs brings on obesity. The primary cause of Obesity is the storage of too much energy and triglycerides in adipocytes, particularly white adipose tissue (WAT). In addition to modifying one’s lifestyle, anti-obesity medicines are increasingly used as adjuvant therapy. Flavonoids are the major class of compounds having significant biological impacts and health-improving properties. To find novel flavonoid compounds that fight obesity using computational drug design techniques. This work targets 1DI protein to predict new flavonoid compounds that fight obesity. The study uses computational approaches to anticipate potential anti-obesity/inflammatory flavonoid compounds against obesity to prevent WAT differentiation by targeting ID-1, a DNA-binding protein inhibitor. Our study led to the identification of the protein target inhibitor lead CID: 5280443, which was found to be a potent inhibitor of the receptor. According to the findings of this study, this bio-active molecule may be used as a lead for the development of drugs that preferentially fight obesity without interfering with the functions of the human proteasome. The scientific community will benefit from these discoveries, which could aid in the creation of new medications that treat obesity more successfully.